2014
DOI: 10.1016/j.molimm.2014.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Divergent roles of histone deacetylase 6 (HDAC6) and histone deacetylase 11 (HDAC11) on the transcriptional regulation of IL10 in antigen presenting cells

Abstract: The anti-inflammatory cytokine IL-10 is a key modulator of immune responses. A better understanding of the regulation of this cytokine offers the possibility of tipping the balance of the immune response toward either tolerance, or enhanced immune responses. Histone deacetylases (HDACs) have been widely described as negative regulators of transcriptional regulation, and in this context, the primarily nuclear protein HDAC11 was shown to repress il-10 gene transcriptional activity in antigen-presenting cells (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
83
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 31 publications
3
83
0
Order By: Relevance
“…More recently, Youn et al have revealed yet another HDAC—HDAC2 that is involved in silencing of the Rb1 MDSCs(Youn, Kumar et al 2013) which reiterates the importance of investigating these epigenetic factors in the context of MDSC biology. There is also new evidence that HDAC6 and HDAC11 proteins physically interact and are being recruited to the IL-10 gene promoter dictating dynamic transcriptional responses(Cheng, Lienlaf et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…More recently, Youn et al have revealed yet another HDAC—HDAC2 that is involved in silencing of the Rb1 MDSCs(Youn, Kumar et al 2013) which reiterates the importance of investigating these epigenetic factors in the context of MDSC biology. There is also new evidence that HDAC6 and HDAC11 proteins physically interact and are being recruited to the IL-10 gene promoter dictating dynamic transcriptional responses(Cheng, Lienlaf et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence also indicates that HDAC6 is present in the nucleus(14, 15) where it can function as cofactor of specific transcription factors to influence gene promoter activity (14, 15, 18-20). Of note, HDAC6 has been also found to regulate inflammatory and immune responses (21-24).…”
Section: Discussionmentioning
confidence: 99%
“…In the cytoplasm, HDAC6 is recognized as a key regulator of cytoskeleton, cell migration and cell-cell interactions(16) given its effect upon the acetylation status of α-tubulin, Hsp90, and cortactin(17). In the nucleus, HDAC6 has been implicated in the regulation of specific transcription factors and gene promoters(14, 15, 18-20). Importantly, accumulating evidence also points to HDAC6 as playing an important role in regulation of inflammatory and immune responses, in particular at the level of the APC/T-cell immune synapse(21), regulatory T-cell function(22), macrophage responses(23) and aberrant airway inflammation (24).…”
Section: Introductionmentioning
confidence: 99%
“…Different classes of HDACs have distinct activities on histones H2A, H2B, H3, and H4 21. HDAC7 is proinflammatory and stimulates IL-6 expression,22 whereas HDAC6 and HDAC11 suppress anti-inflammatory cytokine, IL-10, expression in antigen-presenting cells 23. In contrast, HDAC2 and HDAC3 are anti-inflammatory and suppress proinflammatory cytokine gene expression.…”
Section: Discussionmentioning
confidence: 99%